A Standardized Staining Protocol for L1CAM on Formalin-Fixed, Paraffin-Embedded Tissues Using Automated Platforms. Issue 2 (April 2014) - Fogel, Mina; Harari, Ayelet; Müller-Holzner, Elisabeth; Zeimet, Alain G.; Moldenhauer, Gerhard; Altevogt, Peter
The L1 cell adhesion molecule (L1CAM) is overexpressed in many human cancers and can serve as a biomarker for prognosis in most of these cancers (including type I endometrial carcinomas). Here we provide an optimized immunohistochemical staining procedure for a widely used automated platform (VENTANA™), which has recourse to commercially available primary antibody and detection reagents. In parallel, we optimized the staining on a semi-automated BioGenix (i6000) immunostainer. These protocols yield good stainings and should represent the basis for a reliable and standardized immunohistochemical detection of L1CAM in a variety of malignancies in different laboratories.